Effets de la salinité et de Botrytis cinerea sur les comportements écophysiologique et biochimique de la tomate (Lycopersicon esculentum Miller) - BOUMAAZA Boualem (My University, 2016)
In arid and semi arid regions, the soil salinization is a major constraint to growth and crop development and represents one of the major agronomic challenges. Agro-meteorological conditions in these regions are favorable to the development of crop diseases often caused by fungi.. The aim of this work is the study under physiological and biochemical plans, the tolerance of tomato to salt stress, to infection by Botrytis cinerea and to their combined actions. In this case, the salinity-Botrytis interaction is considered on the case of gray mold of tomato. The results obtained show that the salt stress leads to an inhibition of the germination of the tomato, resulting in a considerable decrease in the percentage of germination. Tomatoes respond to salt stress or infection of Botrytis cinerea by a deficiency of growth in size and weight dry and cool. In this case, the effect of salinity is manifested by an acceleration of the in vitro development of Botrytiscinerea and for in vivo stimulation of the water content of the plant. Physiological and morphological changes caused by the two types of stress: salinity and/or Botrytis cinerea are subjected to biochemical analysis. Indeed, their effects induce stimulation of chlorophyll pigments. Under NaCl, the activity of total protein seems to have a negative effect, while that of Botrytis has no effect on protein activation. In addition, the rate of total free amino acids revealed a specific accumulation exerted by the pathogen. Under these conditions, a bio-protector against to gray mold of tomato is advocated by an antagonistic strain of Trichoderma harzianum. The salinity stimile the action of the latter against Botrytis cinerea observed on the water content and fresh weight of crop plants compared with the witness.
Keywords: salinity, Botrytis cinerea, tomato grey mold, resistance, stress, behavior